P244 Prognostic Value of post-biological induction fecal calprotectin concentration on the long-term outcomes of Crohn's disease. (30th January 2023) - Gagnaire, M; Bendavid, C; Dewitte, M; Brunet, T; Desfourneaux, V; Bordet, M; Siproudhis, L; Bouguen, G
Abstract: Background: Endoscopy remains the gold standard in Crohn's disease (CD) to assess mucosal healing but remains invasive and costly. Mucosal healing is the target to reach in current therapeutic strategies because of its association with improve CD outcomes. Fecal calprotectin is still only a surrogate marker due to the lack of data on its ability to predict disease progression. The main objective of this study is to assess whether the value of fecal calprotectin after introduction of biologic is predictive of long-term outcomes of Crohn's disease. Methods: From a prospective database, all patients followed for Crohn's disease in a tertiary referral center were assessed. We included those in whom fecal calprotectin was measured 3 to 6 months after the introduction of a biologic. Patients were separated into two groups according to the value of fecal calprotectin (more or less than 250 µg/g). Disease outcome was assessed by a composite criterion including: the need for abdominal surgery, progression to complicated phenotype (B2, B3) and a change in therapy due to non-response. Results: A total of 198 fecal calprotectin were measured within 3 to 6 months after introduction of biotherapy. Our study population was 61% female (n=120) with a mean age of 39 years. The average duration of the disease was 10 years, 41% (n=82) had never received biotherapy. The treatment initiated was an anti-TNF in 59% of cases (n=117), ustekinumab (n=64; 32%) or vedolizumab (n=17; 9%). A total of 127 (64%) fecal calprotectin were below 250 µg/g. We identified a strong association between postinduction fecal calprotectin value and the long-term outcome in Crohn's disease patients. Fecal calprotectin was significantly associated with clinical remission without steroids at 1 year from initiation of treatment (p=0, 014). In our population, 20 (10%) patients required surgery, 45 (23%) required a change in treatment, 13 (7%) had a change in phenotype and 61 (31%) had at least one of the three events described above. A fecal calprotectin level above 250 µg/g was associated with more abdominal surgery, phenotype and treatment change (HR 2.47 [1.4; 4, 36] p:0, 0018) (figure 3). In the subgroup of 82 (41%) patients with an available and elevated fecal calprotectine concentration before treatment initiation, the prognostic value of post-induction fecal calprotectin was even better (HR 4, 83 [2, 02; 11, 6] p<0, 001) (figure 1). Fecal calprotectin was the only factor significantly associated in uni and multivariate with long-term disease outcome. Conclusion: Post induction fecal calprotectin seems to be a good prognostic marker of long-term evolution of Crohn's disease. These data could lead to limit the use of colonoscopy currently recommended to 6 to 9 months after the start of treatment.